Etiological identification and biological characteristics of recurrent melioidosis: report of 1 case - YANG Wenbo (Editorial Office of Journal of Third Military Medical University, 2021)
Objective To analyze and explore the possible adaptive mechanisms that Burkholderia pseudomallei (B. pseudomallei) could long-term reside in the host cells based on the systematic etiological identification and biological characteristics of a patient with recurrent melioidosis. Methods The 2 B. pseudomallei strains isolated from the same patient at an interval of 5 years were performed for microbiological identification and genome sequencing, and the sequencing data were further analyzed by multilocus sequence typing (MLST), phylogenetic tree analysis of homologous alignment, single nucleotide polymorphism (SNP) analysis and insertion-deletion (Indel) analysis, respectively. Furthermore, the intracellular survival of the 2 clinical isolates of B. pseudomallei were examined at different times by counting the viable bacteria in the A549 cells. Two-dimensional electrophoresis (2-DE) and mass spectrometry was employed to analyze the protein expression of 2 strains of bacteria. Results The 2 clinical isolates had a whole genome of about 7.12 Mb, and up about 5 000 Clusters of Orthologous Groups (COG) annotations, and was identified as sequence type (ST) 58 by MLST analysis. Phylogenetic analysis of homologous alignment showed that they were located in the same branch and were closely related to other B. pseudomallei isolates from China. SNP/Indel analysis indicated that there were 114 SNP sites and 55 Indel sites in the recurrent strain. The results of 2-DE displayed that the expression levels of 68 proteins in the recurrent strain were significantly changed compared with the primary strain. The intracellular bacterial load of recurrent strain was significantly increased compared to the primary strain in A549 cells(P < 0.05). Conclusion Based on a series of studies with genomics, proteomics and ability of intracellular survival of the 2 clinical isolates of B. pseudomallei, the bacterium may evolve slightly under the long-term selective pressure of the organism, and adapt to the host environment for its own survival through the regulation of bacterial transcription, secretion system, drug resistance and energy metabolism.